VD_FINDINFO Arrêt / 2015 / 548 vom 6. Juli 2015 - VD Tribunal cantonal (2015)
DROIT D'OBTENIR UNE DÉCISION, PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE | 29 al. 1 Cst., 56 al. 2 LPGA, 94 al. 1 let. c LPA-VD